Britt-Marie was here [large type] : a novel - Backman, Fredrik, 1981- (Thorndike Press Large Print, 2016)
Britt-Marie is a socially awkward, fussy busybody who is used to being organized. When she walks out on her cheating husband and gets a job as caretaker of the dilapidated recreation center in Borg, she is woefully unprepared for the changes. But as she takes on the task of leading the supremely untalented children's soccer team to victory, she just might find a place she belongs.